Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.31487/j.jdoa.2020.01.05
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dental Enamel Pre-Etching for Self-Etching Adhesives According to their Primer pH: An In Vitro Bond Strength, Etching Pattern and Adhesive Failure Evaluation

Abstract: Dental enamel pre-etching before the application of a self-etching adhesive (SEA) has different effects depending on the pH of the adhesive acidic monomer, being not always beneficial. This study aimed to evaluate the shear bond strength (SBS), etching pattern, and fracture type of different acidity SEAs, with and without previous phosphoric acid etching. One-hundred-sixty bovine incisors were subjected to SBS testing with the following adhesive systems: Adper-Prompt-L-Pop (APLP) (strong acidity), Futurabond N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This may explain the superior margin integrity of composite restorations after pre-etching both sound and demineralized enamel with phosphoric acid. A recent study found that the effect of enamel pre-etching with phosphoric acid on the bond strength of self-etch adhesives differs according to the primer pH [ 38 ]. In their study, the authors observed a significant increase in enamel bond strength after pre-etching enamel with phosphoric acid when ‘mild’ or ‘intermediately strong’ adhesives were subsequently applied, but not when a ‘strong’, i.e., highly acidic, adhesive was used [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain the superior margin integrity of composite restorations after pre-etching both sound and demineralized enamel with phosphoric acid. A recent study found that the effect of enamel pre-etching with phosphoric acid on the bond strength of self-etch adhesives differs according to the primer pH [ 38 ]. In their study, the authors observed a significant increase in enamel bond strength after pre-etching enamel with phosphoric acid when ‘mild’ or ‘intermediately strong’ adhesives were subsequently applied, but not when a ‘strong’, i.e., highly acidic, adhesive was used [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the effect of enamel pre-etching with phosphoric acid on the bond strength of self-etch adhesives differs according to the primer pH [ 38 ]. In their study, the authors observed a significant increase in enamel bond strength after pre-etching enamel with phosphoric acid when ‘mild’ or ‘intermediately strong’ adhesives were subsequently applied, but not when a ‘strong’, i.e., highly acidic, adhesive was used [ 38 ]. The adhesives used in the present study, iBond Self Etch (pH = 1.6–1.8) and Clearfil SE Bond (pH = 2.0), which benefited substantially from enamel pre-etching, fall into the group of ‘intermediately strong’ and ‘mild’ adhesives, respectively [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trend of self-etch (SE) surface treatment requires less chair time owing to fewer clinical application steps ( Horiuchi et al, 2009 ). SE combines the etching and priming stages using an acidic monomer, eliminating the need for separate etching, rinsing, and drying steps ( Horiuchi et al, 2009 , Nicolas-Silvente et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%